MANAJEMEN PELAKSANAAN PROGRAM BIDANG PENANGANAN FAKIR MISKIN PADA DINAS SOSIAL KOTA KENDARI - Adrian Tawai; Muhammad Yusuf; Suryana Mekuo (Universitas Halu Oleo, 2021)
This study aims to find out about the Management of the Implementation of the Program for Handling the Poor at the Kendari City Social Service. The method used in this study is a qualitative descriptive research method by means of observation, interviews and documentation. The results of this study indicate that the management of the implementation of the poor program carried out by the Kendari City Social Service is management carried out by taking into account the level of problems, objectives, strategies, activity programs, results to be achieved and schedule of activities. Likewise, the objectives and strategies are carried out in accordance with the existing activity programs at the Social Service in terms of handling the poor. the existing social masters so that they still need the next stage to be able to accommodate the poor. The schedule of activities is all carried out with an emphasis on the action plans carried out by the Social Service in every activity carried out as well as the existing poor program activities.